Свидание по заданию: [роман] / Галина Куликова - Куликова Галина Михайловна (Галина Куликова, 2016)
Экземпляры: (20160415) / Инвентарный номер: 39153 / Цена: 217.00 / Авт.знак: К 90 / ГРНТИ: 17 / ББК: 84(2Рос=Рус)6